Malassezia Pneumonia: A Rare Complication of Parenteral Nutrition Therapy. (November 2016) - Baker, Richelle M.; Stegink, Ryan J.; Manaloor, John J.; Schmitt, Bryan H.; Stevens, John C.; Christenson, John C.
Malassezia species (formerly known as Pityrosporum ) are part of normal human skin flora and have been associated with benign dermatologic conditions, such as seborrheic dermatitis and tinea versicolor. In rare cases, however, Malassezia has been associated with systemic disease in immunocompromised patients and infants in the neonatal intensive care unit. Malassezia species require long-chain fatty acids for growth and therefore have a known predilection for individuals receiving lipid containing intravenous parenteral nutrition (PN). Systemic infections are characterized by prolonged fevers and illness but can include nonspecific signs and symptoms. We present the diagnosis and management of a rare case of an immunocompetent, nonneonatal, PN-dependent child with Malassezia furfur pneumonia.